Managing maritime safety - Oltedal, Helle; Lutzhoft, Margareta (Routledge, Taylor & Francis Group, 2018)
Shipping is a pillar of global trade, with 90% of the world's trade in goods and raw materials carried by ship. Despite the economic benefits this delivers, maritime operations can be dangerous, and when accidents occur the consequences are serious. This book sets out to provide much needed consolidated knowledge for university level students on maritime safety management, incorporating theoretical, historical, research, operational and design perspectives.